An investigation of the role of caspase-9-interacting proteins in the molecular control of apoptosis - Adrain, Colin (Trinity College (Dublin, Ireland). Department of Genetics, 2001)
Apoptosis is an important homeostatic mechanism that multicellular organisms utilize to delete cells during development and on an ongoing basis in the adult. At the molecular level, this requires the activation of a family of proteolytic enzymes called caspases. Caspases are constitutively present in healthy cells as inactive zymogens (procaspases). In cells stimulated to die, caspases become activated via proteolytic cleavage, mediated by other active caspases. Evidence suggests that because inactive caspases possess a basal level of proteolytic activity, enforced aggregation can stimulate their activation. Through the proteolysis of strategic cellular substrates, active caspases mediate the biochemical and phenotypical changes required during apoptosis.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin